A coiled‐coil protein is required for coordination of karyokinesis and cytokinesis in Toxoplasma gondii. (13th March 2018) - Courjol, Flavie; Gissot, Mathieu
Abstract: Toxoplasma gondii is a unicellular eukaryotic pathogen that belongs to the Apicomplexa phylum, which encompasses some of the deadliest pathogens of medical and veterinary importance. The centrosome is key to the organisation and coordination of the cell cycle and division of apicomplexan parasites. The T. gondii centrosome possesses a particular bipartite structure (outer and inner cores). One of the main roles of the centrosome is to ensure proper coordination of karyokinesis. However, how these 2 events are coordinated is still unknown in T. gondii, for which the centrosome components are poorly described. To gain more insights into the biology and the composition of the T. gondii centrosome, we characterised a protein that resides at the interface of the outer and inner core centrosomes. TgCep530 is a large coiled‐coil protein with an essential role in the survival of the parasite. Depletion of this protein leads to the accumulation of parasites lacking nuclei and disruption of the normal cell cycle. Lack of TgCep530 results in a discoordination between the nuclear cycle and the budding cycle that yields fully formed parasites without nuclei. TgCep530 has a crucial role in the coordination of karyokinesis and cytokinesis.